ANALISA EFEKTIFITAS PROGRAM PROMOSI PERJALANAN UMROH PADA PT AKRAM RIHLAH MUBARAK BEKASI. - FITRIANI FITRIANI; Nurvi Oktiani; IRWIN SUKRISNO (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
The Growing of in Umroh Travel Agent make rigid and strict for Competition,especially about promotion program for marketing, Promotion is one of effort oraim for facing the competitiveness and acquatinance all of product which thecompany have it. Promotion should have done by interesting and creativeprogram, it can be done looking for and attracting for all the customer , on thatground PT Akram Rihlah Mubarak Bekasi is one of Umrah Travel Agent alwaysgive the variety and innovation of the Promotion for the Costumer, and thepromotion which is setting out by the the variety and innovation have been donefor defencing the competitiveness. The research use the qualitative method byusing the Interview, Observation and literature study, PT Akram Rihlah MubarakBekasi need more of strategies which have been done, and as a result the target ofPromotion has been reach out 75% in 2013, 60% in 2014 and 66,6% in 2015,reach out of the target of Promotion considerate between (realization –Planning/Planningx100%), with the result of the target of promotion which havebeen reach out by ground PT Akram Rihlah Mubarak Bekasi, it can makeconclusion, generally the program of promotion have been done effectiveness ,but in the future the company must think of the best alternative for facing thecompetitiveness by more Effective and innovative Strategies